The Effect of Exposure of Cigarette Smoke With Herb Additives on Leukocyte and Lung Histopathology of Mice (Mus musculus) - M Luthfi Ardiansyah; A.A.S.A Sukmaningsih; Inna Narayani (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2021)
Smoking habits have been around since ancient times, but nowadays this habit is considered to be detrimental, especially to health. The impact that is often felt by smokers is difficulty in breathing because the lungs are exposed to cigarette smoke. Cigarette smoke contains about 1015-1017 oxidants or free radicals, as well as 4700 harmful chemicals, including aldehydes / carbonyls, NO2, and SO2. Herbal cigarettes are tobacco cigarettes with added ingredients from plants. Gurah terapi sin cigarettes are herbal cigarettes that are sold commercially. The aim of this study was to determine the effect of gurah cigarette smoking on the leukocytes and lung histology of mice. This study used a comparative method consisting of 3 groups, namely the control was not exposed to cigarette smoke, treatment 1 was exposed to commercial cigarette smoke and treatment 2 was exposed to cigarette smoke with herbal ingredients and each group consisted of 10 replications. The results showed that there were significant differences (p <0.05) regarding the number of cell necrosis, type II pneumocytes, inflammatory cell infiltration, hemorrhage, and alveolar dilation. While the results of the analysis of the number of leukocytes showed no significant difference where p > 0.05. The results showed that there was no significant difference in the number of leukocytes in the control group, treatment 1 and treatment 2 (p > 0.05). herbs containing various kinds of antioxidants cause a tendency for differences in the number of leukocytes where there is a decrease in the number of lymphocytes and neutrophils and an improvement in the histopathological structure of the lung against type I pneumocyte cell necrosis, hemorrhage, alveolar dilation, type II pneumocyte cell proliferation, and inflammatory cell infiltration in exposed mice. commercial cigarette smoke without herbal ingredients.